Concealment of targeted regions in digital images on mobile devices - Gevorg A. Karapetyan; Hakob G. Sarukhanyan (Изд-во НАН РА)
In this paper we present a framework for robust and effective inpainting of targeted regions in digital images. In framework the modification of frequency selective extrapolation algorithm is used, which provides good quality of concealment. The results of the concealment algorithm of the framework are being compared with the results of the state of art inpainting methods which are included in openCV library available for mobile devices. The framework is implemented for Android OS. For selection of targeted regions in digital images the advance of Bézier curves is used. The effectiveness of the framework has been tested on various digital images.
Keywords: Mathematics